The Effect Application of Low Intensity Pulse Ultra Sound on Wounds Healing and Angiogenesis of Diabetes Mellitus Type 2 Rat Model - Budi Susilo; Cahya Yustisia Hasan; Bambang Dwi Raharjo; Tri Wahyu Pangestiningsih (HM Publisher, 2021)
Wound healing disorder are often found in people with diabetes mellitus. Low Intensity Pulse Ultrasound (LIPUS) therapy was developed to accelerate the wound healing process. The purpose of this study was to determine the effect of LIPUS on wound closure and angiogenesis after skin excision in rats model diabetes mellitus type 2.Twenty-four Sprague dawley rats that match the inclusion criteria were made into type 2 diabetes mellitus by injecting Nicotinamide and Streptozotocin, then devided into six group: DM3, DM7, DM14, DML3, DML7, DML14, with 4 rats each. All rats were made excision wound with punch biopsy in the back area. DML group receive LIPUS therapy in the wound area (frequency 3 MHz, intensity 0,5 W/cm 2 , duty cycle 20%, duration 3 minutes every day) for three days (DML3), seven days (DML7) and fourteen days (DML14). Wound area was measured and the tissue was staineing with hematoksciline eiosin to observe the density of angiogenesis.Two Way ANOVA used to to analyze the differences in the variable wound area and angiogenesis density, Post Hoc LSD to analyze the differences in variables between groups and the day of observation, showed the area of the wound in the DML was lower than in the DM group significant on day 3 and 7, whereas the density of the angiogenesis in DML group was higher than DM group significant on day 7 and 14. The Pearson test showed a correlation between the wound closure and the angiogenesis density (p = 0,000; r = -0,785). Conclusion: LIPUS therapy accelerate wound closure on day 3 and 7and increase the density of angiogenesis on day 7 and 14.